(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
The prevalence of asthma symptoms was studied by questionnaire screening using the adapted international ISAAC questionnaire among 1250 school-age children in two age groups – 7-8 years old (parents of children were surveyed) and 13-14 years old (children were surveyed) in the Turakurgan , Chust districts of the Namangan region, as well as in the city of Namangan, the Republic of Uzbekistan.